Effects of selenium nanoparticles on cadmium uptake, selenium transformation, and metabolomics in Agaricus Blazei murill - Nana Luo; Baojiao Wang; Rui Yu; Guoshuang Chen (Scientific Reports)
Abstract Selenium nanoparticles (Se NPs) primarily reduce cadmium content in plants. However, the mechanism by which Se NPs affect the Cd content in edible mushrooms is unknown. This study addressed this by exogenously adding Se NPs and Cd(NO3)2 to the cultivated substrates of Agaricus blazei Murill (AbM). The results indicated that Cd was easily enriched in the AbM fruiting body, while adding Se NPs significantly decreased the Cd content of AbM by 48.7–69.4%. The percentages of Cd in cell wall fraction (Fw), soluble fraction (Fs), and organelle fraction (Fo) reached 82.9–95.8%, 3.6–15.7%, and 0.6–3.2%, respectively. Se NPs reduced Cd toxicity to AbM by alleviating oxidative stress. Se existed in the fruiting body as selenocysteine (SeCys) and selenomethionine (SeMet). Se NPs could significantly affect the type and content of metabolites in the AbM fruiting body. In conclusion, applying Se NPs to cultivated substrates may mitigate Cd toxicity by reducing Cd uptake into the fruiting body, altering the subcellular distribution of Cd, alleviating oxidative stress, and altering the type, content, and biometabolic pathways of metabolites.